2020
DOI: 10.3390/md18020118
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing and Analysis of Thraustochytriidae sp. SZU445 Provides Novel Insights into the Polyunsaturated Fatty Acid Biosynthesis Pathway

Abstract: Thraustochytriidae sp. have broadly gained attention as a prospective resource for the production of omega-3 fatty acids production in significant quantities. In this study, the whole genome of Thraustochytriidae sp. SZU445, which produces high levels of docosapentaenoic acid (DPA) and docosahexaenoic acid (DHA), was sequenced and subjected to protein annotation. The obtained clean reads (63.55 Mb in total) were assembled into 54 contigs and 25 scaffolds, with maximum and minimum lengths of 400 and 0.0054 Mb, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…These are the polyketide synthase (PKS) system found in marine bacteria ( Shewanella sp., [ 30 ]; Vibrio sp., [ 31 ]; Photobacterium profundum , [ 32 ]) and in some thraustochytrids ( Schizochytrium sp., [ 33 ], Thraustochytrium sp. SZU445 [ 34 ]), and the elongase-desaturase system (ω3- and ω6-pathways) (shown in Figure 2 ). Precursors of ω6- and ω3-pathways (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…These are the polyketide synthase (PKS) system found in marine bacteria ( Shewanella sp., [ 30 ]; Vibrio sp., [ 31 ]; Photobacterium profundum , [ 32 ]) and in some thraustochytrids ( Schizochytrium sp., [ 33 ], Thraustochytrium sp. SZU445 [ 34 ]), and the elongase-desaturase system (ω3- and ω6-pathways) (shown in Figure 2 ). Precursors of ω6- and ω3-pathways (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ]; Thraustochytrium sp. SZU445 [ 33 ]), the synthesis of long-chain ω-3 PUFA from acetyl-ACP and malonyl-ACP is accomplished by polyketide synthase (PKS) systems, also known as PUFA synthases. Our results implied that the synthesis of long chain ω-3 PUFA in RT2316-16 was not due to a PKS system.…”
Section: Discussionmentioning
confidence: 99%
“…PKS pathway domains are likely involved in the production of DHA, such as AT, DH, MT and ER [75,76]. Genomic and transcriptomic analysis have shown that Thraustochytrids contained some key enzymes of PKS system such as 3-ketoacyl-synthase (KS), ketoreductase (KR), and enoyl reductase (ER) [26]. As a probable source of high-value DHA, the PKS pathway is important in DHA biosynthesis, as genes related to the PKS pathway were mined in the transcriptome study of wild Aurantiochytrium sp.…”
Section: Pks Pathwaymentioning
confidence: 99%
“…Genomic and transcriptomic analysis revealed that both the FAS and PKS pathways of PUFA production were incomplete in Thraustochytrids strains [38]. The dehydratase and isomerase enzymes were not detected in the Thraustochytrids strain SZU445 [26]. Although FAD12, FAD4, and FAD5 have been reported in Thraustochytrids, some Thraustochytrids only contains the desaturase not belonging to the FAS pathway, such as FAD6 [39].…”
Section: Introductionmentioning
confidence: 99%